A method of hold baggage security screening system throughput analysis with an application for a medium-sized airport. (March 2018) - Skorupski, Jacek; Uchroński, Piotr; Łach, Adrian
Highlights: Hold baggage security screening (HBSS) may be a critical factor in processing aircraft at airports. HBSS system throughput analysis requires a microscale model. Colored, timed Petri nets were used to model HBSS system. HBSS system throughput was determined for many organizational variants and interferences. General recommendations for a medium-sized airport were proposed. Abstract: The hold baggage security screening (HBSS) is one of the essential steps in a pre-flight operation process. With the continuous increase in the overall air traffic volume, the development of security screening (and control) technologies, and the changes in applicable regulations of law, the structure and equipment of HBSS systems require frequent upgrades. In order to make good, effective decisions about the upgrades, airport management requires tools for quantitative determination of their results. The aim of this work is to analyse the HBSS system throughput. The analysis can serve as an aid in airport management in on-the-go solving of operating issues and making decisions about HBSS upgrades. A mathematical model was established for the analysis in the form of a coloured timed Petri net, and implemented in a computer-aided solution. It was a microscale simulation model, in which every piece of hold baggage is localised in time and with a resolution of a single belt conveyor. The computer-simulated experiments completed with the model helped (i) determine the actual throughput of the HBSS system operated at the Katowice International Airport, (ii) determine the effects of disturbances on the HBSS system operation, (iii) evaluate the impact of the time windows available to SSO (security screening operators), the SSO's work organisation and the efficiency of automatic security screening on the HBSS system throughput, and (iv) determine the throughput for specific alternative variants of the HBSS organisation, including doubled automatic security screening. These results allow a conclusion, that a four-level HBSS system, which includes automatic security screening, two SSO screening levels based on X-ray imaging, and manual control is an HBSS solution adequate for a regional medium-sized airport. It was also found that, given the growth of airport facility complexity and area, an increase of HBSS throughput is viable rather not by improving the capacity of specific HBSS components, but by deploying them in parallel processing lines. The highest throughput growth potential lies in parallel deployment of automatic security screening lines.